Contrast‐Enhanced Sonography for Detection of Secondary Lymph Nodes in a Melanoma Tumor Animal Model. (1st June 2014) - Liu, Ji-Bin; Merton, Daniel A.; Berger, Adam C.; Forsberg, Flemming; Witkiewicz, Agnieszka; Zhao, Hongjia; Eisenbrey, John R.; Fox, Traci B.; Goldberg, Barry B.
Abstract : Objectives: To investigate the use of contrast‐enhanced ultrasound imaging (US) for detection of secondary lymph nodes (LNs) in a naturally occurring melanoma swine model compared to surgery and pathologic assessment. Methods: Twenty‐seven Sinclair swine were studied. The perfluorobutane microbubble contrast agent Sonazoid (GE Healthcare, Oslo, Norway) was administered (1.0 mL total dose) around the melanoma, and contrast‐enhanced US was used to localize contrast‐enhanced sentinel lymph nodes (SLNs). Then Sonazoid (dose, 0.25–1.0 mL) was injected into the SLNs to detect contrast‐enhanced efferent lymphatic channels and secondary LNs. After peritumoral injection of blue dye, a surgeon (blinded to the contrast‐enhanced US results) performed a radical LN dissection. Contrast‐enhanced US was used to guide removal of any enhanced secondary LNs left after radical LN dissection. Clustered conditional logistic regression analyzed the benefit of contrast‐enhanced US–directed secondary LN dissection over radical LN dissection using pathologic findings as the reference standard. Results: A total of 268 secondary LNs were resected, with 59 (22%) containing metastases. Contrast‐enhanced US detected 92 secondary LNs; 248 were identified by radical LN dissection; and 68 were identified by both methods. Metastases were detected in 20% (51 of 248) and 40% (37 of 92) of the secondary LNs identified by radical LN dissection and contrast‐enhanced US, respectively. Thus, secondary LNs detected by contrast‐enhanced US were nearly 5 times more likely to contain metastases than secondary LNs removed by radical LN dissection (odds ratio, 4.8; P < .0001). Twenty‐two of the 180 secondary LNs (12%) identified only by radical LN dissection contained metastases, whereas contrast‐enhanced US identified 20 secondary LNs after the surgeon completed the radical LN dissection, of which 8 (40%) contained metastases. Conclusions: Secondary LNs can be detected by using contrast‐enhanced US after injection of Sonazoid into SLNs. Secondary LNs detected with contrast‐enhanced US are significantly more likely to contain metastases than those removed by radical LN dissection.